2014
DOI: 10.1121/1.4883364
|View full text |Cite
|
Sign up to set email alerts
|

From acoustic descriptors to evoked quality of car door sounds

Abstract: This article describes the first part of a study aiming at adapting the mechanical car door construction to the drivers' expectancies in terms of perceived quality of cars deduced from car door sounds. A perceptual cartography of car door sounds is obtained from various listening tests aiming at revealing both ecological and analytical properties linked to evoked car quality. In the first test naive listeners performed absolute evaluations of five ecological properties (i.e., solidity, quality, weight, closure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
2
8
0
1
Order By: Relevance
“…Further listening tests were then run, using the synthesized stimuli in order to relate the signal parameters to the perceived quality. Results showed that the energy and the damping of the door impact linked to the evocation of the weight of the door, and the elapsed time between the four impacts related to the evocation of a well-closed door was found to mediate the perception of solidity and quality of the car (Bezat et al 2014). This study confirms that signal invariants evoking the solidity and quality of a car can be identified.…”
Section: Fig 3 Relation Between the Sensory Descriptors (Bonm Ke Isupporting
confidence: 72%
“…Further listening tests were then run, using the synthesized stimuli in order to relate the signal parameters to the perceived quality. Results showed that the energy and the damping of the door impact linked to the evocation of the weight of the door, and the elapsed time between the four impacts related to the evocation of a well-closed door was found to mediate the perception of solidity and quality of the car (Bezat et al 2014). This study confirms that signal invariants evoking the solidity and quality of a car can be identified.…”
Section: Fig 3 Relation Between the Sensory Descriptors (Bonm Ke Isupporting
confidence: 72%
“…In recent years, vehicle sound quality has been extensively studied, such as vehicle interior noise, 1, 2 engine noise, 3,4 door closing sound, 5,6 vehicle suspension shock absorber rattling noise, 7 horn sound, 8 and warning of electric vehicle. [9][10][11] These studies include two major parts: subjective evaluation and objective evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the sound heard when opening a beer can could give consumers a pleasant feeling so that they might be disposed to drink the beverage. The sound heard when closing an automobile's door is designed to project a sense of luxury [2,3]. We subconsciously realize that a photograph was taken when we hear the "snapshot" sound of a digital camera, even though the sound is not necessary for the camera to function [4].…”
Section: Introductionmentioning
confidence: 99%